PROGRAM NIKAH BALAI SEBAGAI INTERVENSI SOSIAL BERBASIS PENDIDIKAN NONFORMAL UNTUK PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DI KOTA BENGKULU - Anggraini, Aria Septa; Putra, Ari; Sofino, Sofino (Comm-Edu (Community Education Journal), 2025)
This study examines the implementation and impact of the Nikah Balai Program organized by the Office of Women's Empowerment and Child Protection, Population Control, and Family Planning (DP3AP2KB) of Bengkulu City. As a form of non-formal education-based social intervention, this program aims to empower women and protect children in underprivileged families by overcoming economic and administrative barriers to marriage that is valid according to religion and the state. The research uses a qualitative descriptive approach with a focus on the 2024 implementation, which facilitated the marriage process and legal documents for seven underprivileged couples in Bengkulu City. This program applies the “Six in One” model, which includes financing the procession, KUA administration, dowry, population documents, and family education. Data was obtained through documentation, observation, and interviews with stakeholders and beneficiaries. The results of the study show that this program not only legalizes marriage status and updates population documents, including E-Simil certificates, but also increases family awareness, strengthens the position of women, and guarantees children's rights.